Learning strategies of undergraduate nursing students during the COVID-19 pandemic - Ana Carolina Bezerra de Lima; Danielle Christine Moura dos Santos (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the learning strategies used by nursing students from a public university, in remote teaching, during the COVID-19 pandemic. Methods: a cross-sectional study developed with nursing students who attended remote teaching classes. The sample was obtained by convenience and data were collected online, with 112 participants. Student and Mann-Whitney tests were performed for data analysis. Results: the most frequently used learning strategies were self-regulatory and cognitive. There was moderate use of interpersonal help-seeking and emotional control strategies. Male students, with a private study environment and good internet connection, used emotional control strategies more frequently. Conclusions: self-regulatory and cognitive learning strategies, appropriate for higher education, were frequently used by nursing students, which is an important tool for adapting these students to the university context.